A literary text conscious perception by a reader of V. N. Rudnev - V. N. Rudnev (Библиосфера)
The author analyzes the conscious perception of a literary text by students. He believes that perception is the willingness and desire to know the text author's world by a subject, a reader. In this regard it is proposed to pay attention to the educational standard competences aimed to form readers’ consciousness, activity and communication.